Adequacy of care management of patients with polyhandicap in the French health system: A study of 782 patients. - Marie-Christine Rousseau; Thierry Billette de Villemeur; Sherezad Khaldi-Cherif; Catherine Brisse; Agnès Felce; Karine Baumstarck; Pascal Auquier; French Polyhandicap Group (PLoS ONE, 2018)
Background The aims of this study were 1) to describe the health profiles and care management of polyhandicapped patients according to 2 modalities, specialized rehabilitation centers (SRC) and residential facilities (RF), and 2) to estimate the adequacy of care management of these patients. Methods This was an 18-month cross-sectional study including patients with a combination of severe motor deficiency and profound intellectual impairment. The patients were from 4 SRC and 9 RF. The following data were collected: sociodemographics, health status, care management, and adequacy of care management. Results A total of 782 patients were included: 410 (52%) were cared for in SRC and 372 (48%) in RF. Global objective adequacy (health severity and age category) was higher for patients cared for in SRC compared with patients cared for in RF (57 vs. 44%, p< = 10-3). Global subjective adequacy (self-perception of the referring physician and request of change in structure) was higher for patients cared for in SRC in comparison with patients cared for in RF (98 vs. 92%, p< = 10-3). Conclusions This study provides key elements of adequacy of care management modalities for polyhandicapped patients in France. Trial registration ClinicalTrials.gov NCT02400528.